Systematic review with meta‐analysis: mortality in acute severe ulcerative colitis. Issue 1 (10th December 2019) - Dong, Catherine; Metzger, Marie; Holsbø, Einar; Perduca, Vittorio; Carbonnel, Franck
Summary: Background: Acute severe ulcerative colitis (ASUC) is a life‐threatening condition. Mortality in ASUC decreased in published series but there is uncertainty as to whether this also applies to the real‐life setting. Aim: To perform a systematic review and meta‐analysis of mortality in ASUC in studies from referral centres and in population‐based studies, separately and combined. A second aim was to identify risk factors of mortality in ASUC. Methods: We searched pubmed and embase from 1998 to 2016, to identify studies that reported 3‐month or 12‐month mortalities of acute UC in adult patients treated in referral centres, and in population‐based studies. Results: Six population‐based studies with 741 743 patients and 47 referral centre‐based studies with 2556 patients were included. The pooled 3‐month and 12‐month mortalities were respectively 0.84% and 1.01%. Advanced age was significantly associated with both 3 month and 12 month mortalities (OR = 1.15 per year, 95% CI: 1.10‐1.20 and OR = 1.19 per year, 95% CI: 1.15‐1.23 respectively). The pooled 3‐month and 12‐month mortalities were 0.78% and 0.85% in studies with median age of less than 50 and 2.81% and 4.17% in studies with median age of 50 or more, respectively. After adjustment for age, 3‐month and 12‐month mortalities did not differ between population‐based and referral centre‐based studies. Conclusions: Mortality in acute severe ulcerative colitis is approximately 1%; it is higher in older patients. Efforts should be made to improve the care of elderly patients with severe UC. Abstract : Audio Podcast